2012
DOI: 10.1016/j.colsurfb.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of starvation on the transport of Escherichia coli in saturated porous media are dependent on pH and ionic strength

Abstract: In this research, we investigate the effects of starvation on the transport of Escherichia coli K12 in saturated porous media. Particularly, we examine the relationship between the starvation effects and the pH and ionic strength of the electrolyte solutions used for cell starvation. E. coli K12 was cultured using either Luria-Bertani Miller (LB-Miller) broth, which contained 10 g/L of NaCl, or LB-Luria broth, which contained 0.5 g/L of NaCl. As both types of broths had similar pH (~7.2) they differed in ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
2
11
1
Order By: Relevance
“…Conversely, Walczak et al (2012) found that cell mobility increased with an increase in pH and a decrease in ionic strength, as well as when the biofilm was additionally starved for 4-25 h. This could be the scenario observed in our experiments, as switching from NM to electrolyte resulted in an increase in pH (from 7 to 8) and a decrease in ionic strength (NM contains a high salt concentration). However, in experiments conducted by Walczak et al (2012) the cell culture was injected into sand-packed columns for only 60 min, which could be insufficient for cell adhesion to sand grains. Yang et al (2013) demonstrated that biofilms grown in sand columns, subjected to minimal nutrient medium and high levels of exposure to dissolved zinc for one week still maintained good cell viability.…”
Section: Influence Of Biofilms On Nanoparticle Transportcontrasting
confidence: 56%
See 1 more Smart Citation
“…Conversely, Walczak et al (2012) found that cell mobility increased with an increase in pH and a decrease in ionic strength, as well as when the biofilm was additionally starved for 4-25 h. This could be the scenario observed in our experiments, as switching from NM to electrolyte resulted in an increase in pH (from 7 to 8) and a decrease in ionic strength (NM contains a high salt concentration). However, in experiments conducted by Walczak et al (2012) the cell culture was injected into sand-packed columns for only 60 min, which could be insufficient for cell adhesion to sand grains. Yang et al (2013) demonstrated that biofilms grown in sand columns, subjected to minimal nutrient medium and high levels of exposure to dissolved zinc for one week still maintained good cell viability.…”
Section: Influence Of Biofilms On Nanoparticle Transportcontrasting
confidence: 56%
“…Some studies claim that short-term starvation of a biofilm increases cell attachment (Cunningham et al, 2007). Conversely, Walczak et al (2012) found that cell mobility increased with an increase in pH and a decrease in ionic strength, as well as when the biofilm was additionally starved for 4-25 h. This could be the scenario observed in our experiments, as switching from NM to electrolyte resulted in an increase in pH (from 7 to 8) and a decrease in ionic strength (NM contains a high salt concentration). However, in experiments conducted by Walczak et al (2012) the cell culture was injected into sand-packed columns for only 60 min, which could be insufficient for cell adhesion to sand grains.…”
Section: Influence Of Biofilms On Nanoparticle Transportmentioning
confidence: 98%
“…Research has been performed in recent years to elucidate the factors contributing to or limiting bacterial attachment in a porous media such as sand. These factors include, but are not limited to, cellular dynamics such as conditions for growth (Walker et al, 2005;Yang et al, 2006), composition of the polymeric compounds in the cell matrix (Haznedaroglu et al, 2008;Bolster et al, 2009), cellular surface charge and hydrophobicity (Lutterodt et al, 2009;Foppen et al, 2010;Bolster et al, 2010;Walczak et al, 2012), and the presence of genetic attachment factors and motility (Yang et al, 2008;Lutterodt et al, 2009;Liu et al, 2011). Other important factors include acclimation time of cells (Castro and Tufenkji, 2007;Haznedaroglu et al, 2008), temperature (Castro and Tufenkji, 2007), ionic strength (Bolster et al, 2006), and media characteristics such as particle size and composition (Bradford et al, 2006;Bolster et al, 2009), hydraulic conductivity (Levy et al, 2007), and moisture content (Foppen and Schijven, 2006;Jiang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This size fraction was selected because it represents a major portion of natural porous media and clean quartz sands have been frequently utilized to investigate microbial transport within the subsurface system [20][21][22]. Following each cleaning step, the sands were thoroughly rinsed with deionized water.…”
Section: Column Transport Experimentsmentioning
confidence: 99%